2020
DOI: 10.1002/hfm.20839
|View full text |Cite
|
Sign up to set email alerts
|

Perceived trust in artificial intelligence technologies: A preliminary study

Abstract: Artificial intelligence (AI) is becoming increasingly prevalent in all spheres of society. Still, the perception of AI from users and customers remains the main barrier for its widespread adoption. Previous studies showed that the acceptance of new technologies in society depends on perceived characteristics. This study examined users’ perception of trust, the difficulty of the task, and application performance when using an AI‐based technology. These factors help us to elucidate the mechanisms for building tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…HRM function in organisations where human workers interact, collaborate and perhaps compete with AI-enabled robots in the same teams will need to use such and other similar insights to develop a relatively fair performance appraisal system. This is expected to overcome hesitations and develop trust in such emerging technologies (Bitkina et al , 2020) in order to keep human workers motivated to continue interacting and collaborating with AI-enabled robots, as team members.…”
Section: Ai and Human Workers Interaction: Challenges And Potential H...mentioning
confidence: 99%
“…HRM function in organisations where human workers interact, collaborate and perhaps compete with AI-enabled robots in the same teams will need to use such and other similar insights to develop a relatively fair performance appraisal system. This is expected to overcome hesitations and develop trust in such emerging technologies (Bitkina et al , 2020) in order to keep human workers motivated to continue interacting and collaborating with AI-enabled robots, as team members.…”
Section: Ai and Human Workers Interaction: Challenges And Potential H...mentioning
confidence: 99%
“…A preliminary experiment [30] was conducted to determine the drawing objects corresponding to words and to confirm the difficulty levels of the objects. The preliminary experiment consisted of the selection of target words by five participants who did not participate in the main experiment.…”
Section: ) Drawing Objects and Difficulty Levelmentioning
confidence: 99%
“…Trust was found to be one of the variables with the ability to significantly predict AI technology adoption. The methodology of perceived trust evaluation in AI technology was proposed [30]. It was found that the perceived difficulty, perceived performance, success/failure of the task, and task difficulty were extracted as the important predictors of perceived trust in AI system use.…”
Section: Introductionmentioning
confidence: 99%
“…Trust building in various systems was considered to gain insights into future AI product design (Hengstler et al, 2016; Qin et al, 2020). Difficulty, performance and results of tasks contributed to the perceived trust evaluation (Bitkina et al, 2020). The formation of AI representation, communication in human‐AI, intelligence level of machine and the emotion produced in the interaction were important to shape users' cognitive and emotional trust (Glikson & Woolley, 2020; Troshani et al, 2020;).…”
Section: Literature Reviewmentioning
confidence: 99%